Pengaruh Rasio Terigu, Mocaf, dan Tepung Kacang Hijau Terhadap Mutu Mi Basah - Wafiyah, Wafiyah; Basuki, Eko; Cicilia, Siska (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2025)
Noodles are a food product made from wheat with the addition of other food ingredients. In the current market, people are familiar with various types of noodle products, namely wet noodles, dry noodles, and instant noodles. Wet noodles are a type of noodle that has undergone a boiling process after the cutting stage and before being marketed. This research aimed to determine the effect of the ratio of mocaf, wheat flour, and mung bean flour on the quality of wet noodles. The research method used was a completely randomized design (CRD) with treatments in the form of the ratio of wheat: mocaf: mung bean flour, consisted of MB1 (40%: 60%; 0%); MB2 (40%: 50%: 10%); MB3 (40%: 40%: 20%); MB4 (40%: 30%: 30%); MB5 (40%: 20%: 40%); and MB6 (40%: 10%: 50%). Observation data were analyzed using ANOVA and further tested using the Honest Significant Difference test at the 5% significance level. The results showed that the ratio of wheat flour, mocaf, and mung bean flour gave significantly different effects on moisture content, ash content, protein content, and organoleptic quality of wet noodles. The ratio of 40% wheat flour, 40% mocaf, and 20% mung bean flour was the recommended treatment because it can produce wet noodles with with chemical quality including moisture content 56.19%; ash content 1.09%; protein content 6.07%, and organoleptic quality that is favored by panelists with a slightly chewy texture, no unpleasant taste, no unpleasant aroma, and a pale yellow color.